ChemInform Abstract: Operationally Simple Hydrotrifluoromethylation of Alkenes with Sodium Triflinate Enabled by Ir Photoredox Catalysis. Issue 37 (August 2016) - Zhu, Lei; Wang, Lian‐Sheng; Li, Bojie; Fu, Boqiao; Zhang, Cheng‐Pan; Li, Wei
Abstract: The title reaction works well with terminal alkenes and yields anti‐Markovnikov products.